On a collection of Batraxis Reitter (Coleoptera: Staphylinidae: Pselaphinae) from Hainan Island, southern China - Wang, Dan; Yin, Zi-Wei; Wang, Chun-Xin (Zootaxa, 2016)
Seven species of the genus Batraxis Reitter are described from Hainan Island, southern China: B. bicolor Wang & Yin, sp. n., B. tibialis Wang & Yin, sp. n., B. pilosus Wang & Yin, sp. n., B. spinosus Wang & Yin, sp. n., B. hainanensis Wang & Yin, sp. n., B. minor Wang & Yin, sp. n., and B. simplex Wang & Yin, sp. n. Keys to both sexes of these Batraxis are provided.